2018
DOI: 10.24928/2018/0526
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Labour Productivity in Petrochemical Construction and Maintenance Projects

Abstract: Construction labour is a significant cost factor for petrochemical plant owners and their contractors. Enhancing labour productivity is therefore indispensable for the petrochemical industry in order to achieve sustainable development. Considering the variety of projects undertaken by this industry (i.e. construction and more particularly, maintenance and shutdowns/turnarounds), there is a lack of standard methods for assessing labour productivity. This generates a need for developing productivity assessment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In order to raise the direct work rate of the workers, Sriya Muralidhara et al [47] offered a number of improvement solutions for the non-value-added activities of workers on site. Neve [48] discovered through a case study that using lean tools in construction projects could decrease non-value-added activity and raise labor productivity.…”
Section: Labor Productivity Improvement In Lean Constructionmentioning
confidence: 99%
“…In order to raise the direct work rate of the workers, Sriya Muralidhara et al [47] offered a number of improvement solutions for the non-value-added activities of workers on site. Neve [48] discovered through a case study that using lean tools in construction projects could decrease non-value-added activity and raise labor productivity.…”
Section: Labor Productivity Improvement In Lean Constructionmentioning
confidence: 99%
“…Turning the spotlight to plant shutdown turnaround, Muralidharan et al [7] introduced an activity-analysis approach tailored to site conditions. Their analysis revealed that turnaround personnel expended substantial waiting time beyond direct work, whether for permits, instructions, materials, or QA/QC inspections.…”
Section: Improve Tam Efficiency With Assessment Toolsmentioning
confidence: 99%
“…This section also encapsulates the challenges researchers face in TAM and introduces diverse methodologies for enhancing TAM systems. Techniques such as assessment tools for optimization [6,7], questionnaire surveys [8,9], software aid development, and Risk-based Inspection methods [10,11] have emerged as effective approaches in this context.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Productive work, value-adding work, effective work, direct work CII (2010) proposed seven activity categories: direct work, preparatory work, material handling, tools and equipment, travel, personal and waiting. Several studies directly adopted the CII activity list to analyse labour time utilisation (Gouett et al, 2011;Liu and Golparvar-Fard, 2015a, b;Sheikh et al, 2017;Siriwardana et al, 2017), and some studies further modified the activity list to suit the site conditions or study needs (Karunarathna et al, 2019;Muralidharan et al, 2018). Apart from that, Wandahl and Skovbogaard (2017) also proposed seven activity categories, Production, Talking, Preparation, Transport, Walking, Gone and waiting, which were further adopted by Neve et al (2022) and Neve and Wandahl (2018).…”
Section: Activity Categoriesmentioning
confidence: 99%
“…, 2017), and some studies further modified the activity list to suit the site conditions or study needs (Karunarathna et al. , 2019; Muralidharan et al. , 2018).…”
Section: Overview Of the Activity Sampling Studies In The Constructio...mentioning
confidence: 99%